Shells - Dance, S. Peter (DK Smithsonian handbooks, 2022)
The clearest and sharpest recognition guide to over 500 species of seashells from around the world. Authoritative text, crystal-clear photography, and a systematic approach make this the most comprehensive and concise pocket guide to seashells of the world. Packed with more than 600 full-color photographs of over 500 species of seashells, this handy reference book is designed to cut through the complex process of identification and make it accessible to the average reader. Expertly written and thoroughly vetted, each species entry combines a precise description with annotated photographs to highlight each shell's characteristics and distinguishing features. The entry always includes a distribution map, showing the geographical range of the species, as well as at-a-glance key facts. Packed with detailed information on the shape of each genus, differences between the major classes, and more, this is the clearest identification guide to seashells for beginners and established enthusiasts alike.